Parenting with an accent : how immigrants honor their heritage, navigate setbacks, and chart new paths for their children - Rumer, Masha, 1979- (Beacon Press, 2021)
"A candid portrait of the realities, challenges, and joys many contemporary immigrants confront while raising a new generation of Americans."--